Challenges in the Development of Biological Approaches for the Treatment of Degenerative Disc Disease - Goldberg, Jacob L.; Garton, Andrew; Singh, Sunidhi; Kirnaz, Sertac; Sommer, Fabian; Carnevale, Joseph A.; Atalay, Basar; Medary, Branden; McGrath, Lynn B.; Härtl, Roger (World neurosurgery, 2022)
There are numerous innovative and promising approaches aimed at slowing, reversing, or healing degenerative disc disease. However, multiple treatment-specific impediments slow progress toward realizing the benefits of these therapies. First, the exact pathophysiology underlying degenerative disc disease remains complicated and challenging to study. In addition, the study of the spine and intervertebral disc in animal models is difficult to translate to humans, hindering the utility of preclinical research. Biological treatments are subject to the complex biomechanical environment in which native discs degenerate. The regulatory approval environment for these therapeutics will likely involve a high degree of scrutiny. Finally, patient selection and assessment of outcomes are a particular challenge in this clinical setting.